Economics of the 1% : how mainstream economics serves the rich, obscures reality and distorts policy - Weeks, John, 1941- (London : Anthem Press, 2014)
How much do economists really know? In most cases, they claim to have profound knowledge but in fact understand little and obscure almost everything. Most people are convinced that economics should be left to the 'experts', when they themselves are perfectly capable of understanding it. This book explains that mainstream economics serves the interests of the rich through its logical inconsistency and unabashedly reactionary conclusions. John F. Weeks exposes the myths of mainstream economics and explains in straightforward language why current policies fail to serve the vast majority of people in the United States, Europe and elsewhere. Their failure to serve the interests of the many results from their devoted service to the few.
Preface: Doctor Bob's Third Law -- Introduction: Economic ignorance -- Fakeconomics and economics. Idolatry of competition ; Teflon pseudoscience ; How real markets operate ; Where econfakers dwell ; Fakeconomics and economics: name and shame -- Market worship. What is competition? ; Why markets go bad ; The "labor market" ; Workers cause their unemployment? -- Finance and criminality. Why a financial sector? ; Cost of the financial crisis ; Financial markets: folks like you and me -- Selling market myths. Designing deception ; Resources are scarce ; The supply and demand scam ; Resources abundant, wants limited ; Nonsense of consumer "choice" -- Riches, "sovereignty" and "free trade." Even you can be rich ; Consumer is sovereign ; Everyone gains from free trade -- Lies about the government. Government is a burden ; Wasting money on social(ist) spending ; Markets and governments -- Deficit disorders and debt delirium. Peddling nonsense ; Public and private: debts and deficits ; Calculating public deficits ; Calculating public debt -- Governments cause inflation? Fears of inflation ; What is money? ; Too much money causes inflation? ; What is inflation? ; Why do prices go up? ; Inflation fears: a class act -- Institutionalized misery: austerity in practice. Balanced budget ideology ; Deficit disorder in the land of the free ; Fear and financial market loathing in the UK ; Great euro scam ; 99% in thrall to the 1% -- Economics of the 99% Wealth accumulates and democracy decays ; Fakeconomics and class struggle ; Open debate in economics ; Economics in a decent society ; Implementing economics for the 99% ; "Our future lies before us."
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: United States -- Economic policy; United States -- Economic conditions